Das nicht klassische adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (Pädiatrische Praxis, 2020)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 17-OHP; ACTH test; Cortisol; CYP21A2; Premature pubarche

Das nicht klassische Adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (gynäkologische praxis, 2021)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 17-OHP; ACTH test; cortisol; CYP21A2; premature pubarche

Genotype-phenotype correlations in children and adolescents with nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency. - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, Markus; Binder, Gerhard; Bonfig, Walter; Denzer, Christian; Dunstheimer, Desirée; Salzgeber, Kirsten; Schmidt, Heinrich; Schwab, Karl-Otfried; Voss, Egbert; Wabitsch, Martin; et al. (Molecular and Cellular Pediatrics, 2020)
BACKGROUND: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. AIMS: Description of the phenotype, evaluation of the diagnostics and genotype-phenotype correlation PATIENTS AND METHODOLOGY: Retrospective analysis of the data of 134 patients (age range 0.1-18.6 years) in a multicentre study covering 10 paediatric endocrinology centres in Bavaria and Baden-Württemberg. The data was gathered on site from the medical records. Two hundred and thirty-three alleles with a mutation of the CYP21A2 gene were identified in 126 patients. A genotype-phenotype correlation of the mutation findings was undertaken (C1, severe/mild; C2, mild/mild). Individuals with a heterozygous mutation of the CYP21A2 were also included (C3). The data was collected with the approval of the ethics committee of the University Hospital of Erlangen during the period of 2014 and 2015. RESULTS (MW ± SD): One hundred and seventeen out of 134 patients (115 f, 29 m) were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-SDS on diagnosis was 0.8 ± 1.3 and the BMI-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17OHP concentrations were 14.5 ± 19.1 ng/ml (18 patients < 2 ng/ml). In total, 58.1% mild and 34.7% severe mutations were found. The most common mutation was p.Val281Leu (39.1%); 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the 3 mutation groups. The 17OHP levels (basal and after ACTH) in the standard ACTH stimulation test were highest in group C1 and also significantly higher in group C2 as in C3, the ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). CONCLUSION: Most of the patients have symptoms of mild androgenisation. Male patients are underdiagnosed. Diagnostics are not standardised. Differences between the types of mutations are found in the hormone concentrations but not in phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
EVALuna2:385044

Genotyp-Phänotyp-Korrelationen bei Kindern und Jugendlichen mit nichtklassischem adrenogenitalen Syndrom mit 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, M.; Binder, G.; Bonfig, W.; Denzer, C.; Dunstheimer, D.; Salzgeber, K.; Schmidt, H.; Schwab, K. O.; Voss, E.; Wabitsch, M.; et al. (Monatsschrift Kinderheilkunde, 2020)
Background: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency (NCCAH) is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. Objective: Description of the phenotype, evaluation of the diagnostics, genotype-phenotype correlation. Patients and methodology: Retrospective analysis of the data of 134 patients (age range 0.1–18.6 years) in a multicenter study covering 10 pediatric endocrinology centers in Bavaria and Baden-Württemberg. The data were collected on site from the medical records. In 126 patients 233 alleles with a mutation of the CYP21A2 gene were identified. A genotype-phenotype correlation of the mutation findings was undertaken (C1: severe/mild, C2: mild/mild). Individuals with a heterozygote mutation (C3) were also included in the analysis. The data were collected with the approval of the ethics committee of the University Hospital of Erlangen during the time period of 2014 and 2015. Results (MW ± SD): Out of 134 patients (115 female, 29 male) 117 were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-standard deviation score (SDS) on diagnosis was 0.8 ± 1.3 and the body mass index (BMI)-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17-hydroxyprogesterone (17-OHP) concentrations were 14.5 ± 19.1 ng/ml (18 patients <2 ng/ml). In total 58.1% mild and 34.7% severe mutations were found. The most common mutation (39.1%) was p.Val281Leu and 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the three mutation groups. The 17-OHP levels (basal and after ACTH) in the ACTH test were highest in group C1 and also significantly higher in group C2 than in group C3. The ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). Conclusion: Most of the patients had symptoms of mild androgenization. Male patients were underdiagnosed. The diagnostics were not standardized. Differences between the types of mutations were found in the hormone concentrations but not in the phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
CRIS-Team Scopus Importer:2020-07-24
Keywords: 17-OHP; ACTH stimulation test; Androgenisation; CYP21A2 gene mutations; Premature pubarche